INOVASI TEKNOLOGI AI DALAM PENULISAN ILMIAH: SEBUAH PENGEMBANGAN HANDBOOK - Bayu Kurniawan; Nelyahardi; Hera Wahyuni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study addresses the increasing use of Artificial Intelligence (AI) across various fields, including scientific writing. AI offers several advantages, such as text summarization, grammar checking, automatic citation, and data analysis. However, the utilization of AI in academic writing faces challenges, such as the lack of clear guidelines or a printed manual for its use in an academic context. This research aims to develop a practical Handbook that helps students use AI optimally. The development process involves four stages: preliminary study, product development, validation and revision, and limited trials. The preliminary study, consisting of interviews with students, identified the field's needs. Based on these results, the Handbook was developed and structured according to academic writing standards. The product was validated by experts in content, media, and practitioners. After validation and revision, the Handbook was tested with 20 students to assess its effectiveness. Validation results showed a feasibility score of 90% from content experts, 100% from media experts, and 92% from practitioners. The limited trial resulted in an 83% score, indicating the Handbook’s feasibility. The findings suggest that this Handbook is an effective learning tool, ready to help students and academics understand and use AI optimally and responsibly in scientific writing.